A Structural Bioinformatics-Guided Study of Adenosine Triphosphate-Binding Cassette (ABC) Transporters and Their Substrates - Iqra Younus; Robert C. Ford; Stephen M. Prince (Membranes)
Adenosine triphosphate-binding cassette (ABC) transporters form a ubiquitous superfamily of integral membrane proteins involved in the translocation of substrates across membranes. Human ABC transporters are closely linked to the pathogenesis of diseases such as cancer, metabolic diseases, and Alzheimer’s disease. In this study, four ABC transporters were chosen based on (I) their importance in humans and (II) their score in a structural bioinformatics screen aimed at the prediction of crystallisation propensity. The top-scoring ABC transporters’ orthologs (Mus musculus—mouse ABCB5, Ailuropoda melanoleuca—giant panda ABCB6, Myotis lucifugus—little brown bat ABCG1 and Mus musculus ABCG4) were then expressed in Saccharomyces cerevisiae with a combined green fluorescent protein and polyhistidine tag, enabling visualisation and purification. After partial purification and in the presence of the detergent (n-dodecyl-β-D-maltoside), the kinetic parameters of the ATP hydrolysis reactions of the orthologs were determined, as well as the extent of stimulation of their activity when presented with putative substrates. We discuss the efficiency of such bioinformatics approaches and make suggestions for their improvement and wider application in membrane protein-structure determination.